1984
DOI: 10.1007/bf01852383
|View full text |Cite
|
Sign up to set email alerts
|

Small bowel and liver gas tensions during intravenous vasopressin infusion and 60% oxygen ventilation

Abstract: Vasopressin has been found to significantly decrease tissue pO2 in the gastrointestinal tract and the liver. The aim of this study was to find out whether 60% oxygen ventilation could prevent the tissue hypoxia. Vasopressin was infused i.v. in ten piglets for 60 min. During the first 30 min they were ventilated by room air and for the following 30 min by 60% oxygen, which did not alter the intestinal tissue pO2, but liver pO2 increased to the normal level. The plasma lactate was significantly decreased by 60% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…In fact, AVP has been traditionally employed to decrease perfusion of the hepatosplanchnic system in patients with bleeding esophageal varices (5). Similar to our observations, previous studies demonstrated that AVP not only reduces blood flow in a dose-dependent manner but also decreases small bowel PO 2 and diminishes the arteriovenous oxygen content difference in the gut (11,22,23,34).…”
Section: Discussionsupporting
confidence: 86%
“…In fact, AVP has been traditionally employed to decrease perfusion of the hepatosplanchnic system in patients with bleeding esophageal varices (5). Similar to our observations, previous studies demonstrated that AVP not only reduces blood flow in a dose-dependent manner but also decreases small bowel PO 2 and diminishes the arteriovenous oxygen content difference in the gut (11,22,23,34).…”
Section: Discussionsupporting
confidence: 86%
“…However, during organ harvesting, diuresis is considered a valuable sign of adequate kidney perfusion (8). Also, ADH is known to cause vasoconstriction and even hypoxia in the splanchnic bed (9). The significance of it is obscure in the liver donor.…”
Section: Discussionmentioning
confidence: 99%